SARS-CoV-2 vaccines-induced thrombotic thrombocytopenia: should we consider immuno-hypersensitivity? - Rine Christopher Reuben; Lillian Yami Adogo (Universidade de São Paulo, 2021)
ABSTRACT The coronavirus disease 2019 (COVID-19) pandemic is significantly causing unprecedented clinical, socioeconomic, and public health challenges globally. The successful global administration of effective, safe and sustainable vaccine(s) is widely believed to be crucial in mitigating as well as preventing COVID-19. However, the rising cases of severe adverse events following immunization (AEFI) with COVID-19 vaccines including thrombosis, thrombocytopenia, and in some instances, death have created serious global concerns and could enormously contribute to vaccine hesitancy. Although the complete underlying pathophysiology and immunopathology of the COVID-19 vaccines related to AEFI, including thrombosis and/or anaphylaxis, are yet to be determined, exploring possible immuno-hypersensitivity could be crucial in the mechanisms associated with these reactions, thereby mitigating their occurrences as well as restoring confidence in vaccine administration for a COVID-19 free world.